Interpreting Time in the Qur'anic Text: Between the Cosmic Vision and Narrative Structure - Wisam Abbas Juaijeh Al-Shahmani, Lect. Dr. (lark, 2025)
This study seeks to present a hermeneutical reading of the possible meanings arising between the cosmic vision and the narrative formation in the Qur’anic text, with a focus on time in its two dimensions: textual and real. It aims to uncover the interrelations between these two dimensions and highlight their stylistic and intellectual significance in constructing the Qur’anic narrative, as well as to elucidate their spiritual and epistemological implications.The research is based on the hypothesis that time in the Qur’anic stories is not used as a neutral external frame, but rather as an active and directive element of the narrative act, conveying profound doctrinal and moral meanings.The study begins with a conceptual framework exploring the origins of temporal concepts in philosophy and religion. It then surveys the major intellectual approaches that have attempted to interpret the essence of time, emphasizing the distinctiveness of the Qur’anic cosmic vision in perceiving time as a reality bound to divine movement in creation, resurrection, and judgment.It proceeds to trace the main forms of narrative time in the Qur’anic stories—such as chronological order, flashback, foreshadowing, and time compression—demonstrating how the Qur’anic narrative employs these techniques to achieve semantic density and aesthetic impact, without adhering to a strictly linear sequencing of events.Subsequently, the research investigates the role of time in shaping characters and building plot structures, attempting to illustrate how time intersects with the development of characters and their transformative journeys. It draws on examples such as the stories of Moses and the Wise Servant, the Companions of the Cave, and Joseph (peace be upon them all).The study also explores the moral and didactic dimension of time, highlighting how the Qur’an uses time to instill concepts of accountability, transformation, patience, and ultimate consequence—reinforcing the spiritual and ethical depth of the stories.Finally, the research approaches time from a Qur’anic philosophical perspective, examining how time in the Qur’anic narrative transcends quantitative measures to become part of the divine laws of existence and trial, integrally linked to the Qur’anic vision of creation, history, and resurrection.The study concludes that time in the Qur’anic narrative is not merely a narrative dimension, but a fundamental element through which the Qur’an’s philosophy of human existence and history is manifested. It functions as a vehicle for affirming values, stimulating contemplation, and fulfilling both the aesthetic and admonitory roles of the narrative text.
Keywords: The Holy Qur’an, Cosmic Vision, Narrative, Time